INSURANCE OF THE PROPERTY OF LEGAL ENTITIES (Innovative Technologica: Methodical Research Journal, 2023)
Property insurance classes of the general insurance network. Property insurance of legal entities is provided by insurance companies in accordance with the "Insurance Activity Classifier", class 8 of the general insurance network - "Property insurance against fire and natural disasters", fire, explosion, storm, hurricane, In case of loss or damage of property due to hailstorm, landslide, soil subsidence, erosion, underground water, flood, lightning strike, earthquake, nuclear energy, insurance coverage is provided based on the types of insurance. Also, the 9th class of this classification is related to property insurance, it is called "Property damage insurance". Class 9 includes all types of insurance that provide coverage for loss or damage to property caused by hail, heavy snow or freezing temperatures, burglary and other events not covered by Class 8. It is worth noting that all insurance organizations licensed by the Ministry of Finance of the Republic of Uzbekistan under the 8th and 9th classes have the right to insure the property of legal entities.